A conceptual framework of the relationship between total quality management, corporate social responsibility, innovation capability, and financial performance. (2017) - Manzani, Younès El; Sidmou, Mohamed Larbi; Cegarra, Jean-Jack
Total quality management, corporate social responsibility, and innovation are considered as strategic orientations allowing the achievement of a sustainable competitive advantage. However, there is a gap in the literature regarding the study of the links between these three concepts in a single analysis, the majority of researchers do not gather the study of these three concepts at once, as they do not as well link them to the financial performance. The main purpose of this conceptual paper is to examine the relationship between quality, innovation, corporate social responsibility and financial performance. We are aiming to build a conceptual framework with a particular emphasis on the role that may be played by TQM practices in the development of the bidirectional link between corporate social responsibility-innovation capability, and its impact on the improvement of the firm's financial performance.